A systemic functional grammar of English a simple introduction - Banks, David 1943- (Routledge, 2019)
"Providing a simple - but not simplistic - introduction to the systemic functional grammar of English, this book serves as a launching pad for the beginning student and a review for the more seasoned linguist. With an introduction to systemic functional grammar (SFG) through lexicogrammar and the concept of rankshift, this book is the first introduction to SFG (including Appraisal) with examples exclusively sourced from twenty-first century texts. Written for those learning English and English linguistics as a foreign language, this serves as an easy-to-read introduction or refresher course for systemic functional linguistics"--Provided by publisher.